Mechanistic Details and Conformational Behavior of Selective Peptide Linkage Facilitated by Aun Clusters. Issue 27 (21st July 2020) - Yadav, Sarita; Springborg, Michael; Singhal, Sonal; Molayem, Mohammad; Goel, Neetu
Abstract: The interactions of amino acids Glycine and Alanine with gold clusters, Aun (n=3, 8, 16) have been studied in both gas and aqueous phase within the formalism of density functional theory (DFT). The amino acid binds to the cluster with its amine/carboxyl end securely anchored to the cluster. Selective peptide synthesis has been explored for Glycylglycine (GlyGly) and Glycylalanine (GlyAla) dipeptides in aqueous medium via two different reaction pathways. Path‐ Abstract : In recent time, strategies of peptide synthesis not only allow the scientists to make peptides that are found in biological specimens but also allow them to tap their creativity and imagination to generate unique peptides to optimize a desired biological response. Thus, present study provides barrier‐less transition state vis‐à‐vis an uncatalyzed peptide synthesis that encounters high activation barrier via using Aun clusters.